Hubungan antara Kebiasaan Sarapan dengan Produktivitas Kerja pada Karyawan di PT. Swabina Gatra Tuban - Giantari, Sindy Amalia; Qonitun, Umu; Fuziyah, Lilia Faridatul (Kabar Gizi Indonesia, 2025)
Labor determines the growth and development of the company, besides that labor is the most important asset for a company to run optimally. Companies will produce quality products or services if their workers have a high productivity value. Along with the rapid development of the times, and increasingly fierce competitive conditions, companies compete to maintain their business, therefore companies must know the capabilities of their workforce. The purpose of this study was to determine the relationship between breakfast habits, age and gender with work productivity in employees. This research is an analytical research with a cross sectional time approach. The population is 300 employees of PT. Swabina Gatra Tuban in 2023 with a sample of 171 employees selected through a simple random sampling technique. The independent variables consisted of breakfast habits, age, and gender, the dependent variables of work productivity. Analysis of the study using statistical tests of spearmans correlation. Research shows the results of statistical tests both on the variables of breakfast habits with work productivity, age with work productivity, and sex with work productivity, there is a significant relationship with each having a p-value = 0.000< 0.05. The contribution of energy in breakfast for workers can determine health conditions and physical abilities, while the contribution of inappropriate breakfast energy can reduce labor productivity and will affect company profits. Therefore. It should be emphasized to the workforce the importance of breakfast habits in increasing work productivity.